Track shoe structure optimization of deep-sea mining vehicle based on new rheological calculation formulae of sediment. Issue 4 (4th July 2019) - Xu, Feng; Rao, Qiuhua; Ma, Wenbo
Abstract: Based on compressive and shearing rheological models of the deep-sea sediment simulant, new rheological calculation formulae of traction forces for actual track shoe structures were deduced and the multi-objective structural optimization models were established in order to determine optimal track shoe structural parameters. RecurDyn software with introduction of programed rheological models was used to simulate the moving performances of the tracked mining vehicle before and after optimization. Research results show that the maximum traction force calculated by the new rheological calculation formula is much smaller than that by the Bekker theory and more close to the actual situation. The optimized tracked mining vehicle has larger traction force and smaller sinkage than the original tracked mining vehicle, which verifies the validity of the multi-objective optimization model based on the new rheological calculation formula of track force. It is better to choose the thick-triangle track shoe or the sharp-triangle track shoe when the sinkage or the traction force is considered as a dominant factor, respectively. The new rheological calculation formula of traction force and the multi-objective structural optimization model could provide a theoretical basis for safe operation and optimal design of a tracked mining vehicle.